Analisis Kritis Terhadap Anatomi Teori Strukturalisme Claude Levi-Strauss (Larangan Incest dalam Sistem Pernikahan dan Kekerabatan, serta Relevansinya dengan Pendidikan Islam): Critical Analysis of the Anatomy of Claude Levi-Strauss' Theory of Structuralism (Prohibition of Incest in the Marriage and Kinship System, and Its Relevance to Islamic Education) - Anshori, Isa (Halaqa: Islamic Education Journal, 2019)
Structuralism is not related to empirical reality, but with models built according to empirical reality. That the prohibition of incest in the system of marriage and kinship is universal, applies to all societies, including Muslim societies. Islam forbids marrying fellow relatives who still have blood relations, even more than that, or called mahrom. With the Incest prohibition there will be inter-group exchanges, communication between groups will occur, which will then form a society. If there is no prohibition on incest, there will be no group exchange, which in turn will not result in communication between groups, and a society will not be formed. The kinship system, marriage rules and lineages form a togetherness whose function is to ensure the permanence of social groups, namely by bringing together mutual relationships, namely relationships based on marriage as a network. The process of forming new social groups through marriage between groups that do not have blood relations enabling the occurrence of a richer educational process with values, knowledge and skills, then forming a new, progressive, multiketed civilized society that has strong ties. In Islamic education the form of society that is created is a civilized society that is progressive, universal but has a unity of aqeedah, namely faith and devotion only to Allah SWT.